Seismic response analysis of multiple-frame bridges with unseating restrainers considering ground motion spatial variation and SSI - Shrestha, B.; Hao, Hong; Bi, Kaiming (Multi-Science Publishing, 2015)
Unseating damages of bridge decks have been observed in many previous major earthquakes due to large relative displacement exceeding the available seat length. Steel cable restrainers are often used to limit such relative displacements. Present restrainer design methods are based on the relative displacements caused by the different dynamic characteristics of adjacent bridge structures. However, the relative displacements in bridge structures are not only caused by different dynamic characteristics of adjacent bridge segments. Recent studies indicated that differential ground motions at supports of bridge piers and Soil Structure Interaction (SSI) could have a significant influence on the relative displacement of adjacent bridge components. Thus the present design methods could significantly underestimate the relative displacement responses of the adjacent bridge components and the stiffness of the restrainers required to limit these displacements. None of the previous investigations considered the effects of spatially varying ground motions in evaluating the adequacy of the restrainers design methods. Moreover, the code recommendation of adjusting the fundamental frequencies of adjacent bridge structures close to each other to mitigate relative displacement induced damages is developed based on the uniform ground motion assumption. Investigations on its effectiveness to mitigate the relative displacement induced damages on the bridge structures subjected to spatially varying ground motion and SSI are made. This paper discusses the effects of spatially varying ground motions and SSI on the responses of the multiple-frame bridges with unseating restrainers through inelastic bridge response analysis.